Prediction of antidiabetic effect after gastrectomy with Roux-en-Y reconstruction in patients with gastric cancer and type 2 diabetes. Issue 36 (9th September 2022) - Seo, Seong Ha; Cho, Yongin; Heo, Yoon Seok; Seo, Da Hea; Ahn, Seong Hee; Hong, Seong Bin; Suh, Young Ju; Kim, So Hun
Abstract : This study investigated the antidiabetic outcomes after gastrectomy with long-limb RY reconstruction (LRYR) and the prognostic factors for remission after 1 year in patients with type 2 diabetes (T2DM) and gastric cancer. In 25 Koreans with T2DM and gastric cancer, plasma glucose and insulin levels were measured during a 75 g oral glucose tolerance test, before and 1 week after gastrectomy with LRYR. Patients were examined after 1 year and we defined glycemic control as "remission" when the HbA1c level after 1 year was <6.0% without medication. One year after surgery, 12 patients achieved HbA1c < 6.0% without medication. Among the preoperative indices, the duration of diabetes was shorter in the remission group than that in the non-remission group (median 2.0 [0–6.5] years vs 7.0 [4.5–10.0] years, P = .023). At 1 week after surgery, significant improvements in fasting, 30 minutes, 60 minutes, 90 minutes stimulated glucose levels and insulin resistance (HOMA-IR and Matsuda index) were found only in the remission group. The multivariable logistic regression analysis results showed that higher 30 minutes stimulated glucose level and HOMA-IR index at 1 week after surgery were independent factors for lower odds of 1-year diabetes remission. Shorter duration of diabetes and early postoperative improvements in 30 minutes stimulated glucose level and HOMA-IR were important determinants of long-term antidiabetic outcomes after gastrectomy with LRYR in patients with T2DM and gastric cancer.